Covid-19 worry-free electronic voting: Malaysia future election using blockchain based technology - Syarifah Afifah, Syed Hassan; Fernando, Yudi (2021)
Electronic voting using blockchain based technology is a secure and trusted system where the purpose is to achieve precise results in voting. It includes voter registration, vote casting and ballot counting in a system. Electronic voting using blockchain based technology was developed to ease voters to cast the vote by using smartphones or electronic devices from their remote locations. This technology helps in reducing human errors and shorten the time of ballots counting. It is also an emergency preparedness especially in holding elections during pandemic.